In-situ temperature monitoring of a lithium-ion battery using an embedded thermocouple for smart battery applications. (October 2022) - Gulsoy, B.; Vincent, T.A.; Sansom, J.E.H.; Marco, J.
Abstract: Uncertainty in the measurement of key battery internal states, such as temperature, impacts our understanding of battery performance, degradation and safety and underpins considerable complexity and cost when scaling-up battery components into complete systems. Our research presents a systematic methodology for the engineering of a commercially available cylindrical cell format to accept in-cell instrumentation. We have developed bespoke cell opening methods and unique fixtures that facilitate a reliable instrumentation process. Extensive experimental results are presented that highlight the performance of both the sensor and the lithium-ion battery are not adversely affected by instrumentation. Our modified test cells were evaluated the energy capacity and impedance for a range of different electrical loading conditions and compared to a set of reference or unmodified batteries. The longer-term implications of embedding instrumentation within a battery are also evaluated with cell performance evaluated after a period of calendar and cyclic ageing. Our study demonstrates the importance of internal temperature monitoring during cell operation by comparing internal and surface temperatures measurements. We found that the internal temperature is consistently and notably higher than surface temperature during cell characterisation and when the cell was electrically loaded with a dynamic real-world profile derived from an electric vehicle. No significant effect on the electrochemical performance of the instrumented cells was observed. Measurement data demonstrates that there is a negligible reduction in energy capacity and only a marginal increase in internal resistance. Highlights: Systematic and rigorous methodology developed for cell instrumentation. 21700 cylindrical cells instrumented via bespoke thermocouples – enabling internal temperature sensing. Internal temperature observed to be notably higher than surface temperature. Temperature differential between core and surface diverged as battery state of health decreases. Cell performance verified pre- & post- instrumentation with negligible degradation over the long-term.